Serum Calcium Levels in Stunting Toddlers Ages 24-59 Months - Bayu Anggriani; Rico Januar Sitorus; Rostika Flora; Risnawati Tanjung (Jurnal Kesehatan Islam : Islamic Health Journal, 2022)
Abstract. Stunting is a condition of failure to thrive in children under five due to chronic malnutrition, especially in the First 1,000 Days of Life (DoL). Malnutrition that occurs early in life can lead to failure to thrive, resulting in a shorter than normal child. Good quality food intake is an important component in children's growth, because it contains sources of macro (energy, carbohydrates, protein, fat) and micro (vitamins and minerals) nutrients. Micronutrients that have been proven to be very important to prevent stunting are zinc, iron, vitamin A and iodine. However, several other micronutrients such as vitamin D, calcium and phosphorus also play an important role in children's linear growth. the special function of vitamin D in this case is to help harden bones by regulating so that calcium and phosphorus are available in the blood to be deposited in the process of bone hardening. During growth, the process of bone mineralization often occurs, calcium deficiency will affect linear growth if the calcium content in the bone is less than 50% of the normal content. Lack of calcium in the bones in infants can cause rickets, whereas in children, lack of deposits can cause stunted growth. This research is an observational analytic study with a cross sectional design conducted in Mestong District, Muaro Jambi Regency in March 2022. The research sample was normal and stunted toddlers aged 24- 59 months as many as 41 people taken using proportional consecutive sampling technique. Examination of serum calcium levels was carried out on toddlers using the Calcium (Ca) Colorimetric Assay Kit method. The results showed that there was no difference in serum calcium levels in normal and stunted children